THE FORMATION OF THE REGIMENTS OF THE ACTIVITIES OF INTERNAL AUDITORS - T. Rogulenko (Вестник университета, 2018)
This article deals with the study of internal control of expenses in the oil and gas industry, the formation of approaches to the regulation of internal auditors. The sections of the regulation on internal control: general provisions, objectives and objectives of the audit, basic concepts and denitions, methodological approaches used in assessing the accounting system used in the enterprise, the internal audit program, analytical procedures is substantiated. The use of the developed Provision will allows to conduct an internal audit of costs and cost formation, identify threats and risks associated with violation of the law and payment of penalties.